Pharaoh : a novel of ancient Egypt - Smith, Wilbur A. (Smith, Wilbur A. Ancient Egypt series., 2016)
Taita, the Pharaoh's advisor and hero of Desert God and River God, once again finds himself caught up in a whirlpool of ruthless intrigue that threatens the very foundations of the beloved empire he has pledged his life to protect. Plunged into dangerous and deadly waters more treacherous than the Nile, he must use his intelligence, alchemy, and cunning to protect his Pharaoh and keep safe all he loves.